Skeletal muscle fiber type and morphology in a middle-aged elite male powerlifter using anabolic steroids - Machek, S. B.; Lorenz, K. A.; Kern, M.; Galpin, A. J.; Bagley, J. R. (Journal of Science in Sport and Exercise, 2021)
Powerlifting regularly exposes athletes to extreme stimuli such as chronic heavy resistance training (HRT), and many powerlifters choose to augment their performance with anabolic-androgenic steroids (AAS). However, little is known about the myocellular adaptations that occur from long-term HRT and AAS use, especially into middle age. We were presented with the unique opportunity to study muscle cells from an elite-level powerlifter (EPL; age 40 years) with = 30 years of HRT experience and = 15 years of AAS use. The purpose of this case study was to identify myocellular characteristics [myosin heavy chain (MHC) fiber type, fiber size, and myonuclear content] in EPL, as well as compare these data to existing literature. The participant underwent a resting vastus lateralis muscle biopsy and single fibers were analyzed for MHC content via SDS-PAGE. A subset of fibers underwent MHC-specific imaging analysis via confocal microscopy to identify cell size (cross-sectional area, CSA) and myonuclear domain (MND) size. MHC fiber type distribution was 9% I, 12% I/IIa, 79% IIa, and 0% other isoforms. This pure MHC IIa (fast-twitch) fiber content was amongst the highest reported in the literature. Imaging analysis of MHC IIa fibers revealed a mean CSA of 4218 ± 933 µm2 and MND of 12,548 ± 3181 µm3. While the fast-twitch fiber CSA was comparable to values in previous literature, mean MND was smaller than has been reported in untrained men, implying greater capacity for growth and repair. These findings showcase the unique muscle cell structure of an elite powerlifter, extending the known physiological limits of human muscle size and strength.